Translation of gradations from English into Russian - Farida Ismailova (Research Retrieval and Academic Letters, 2023)
The given article reveals the problem of gradation translation. Pecularities of the problem have been covered and analyzed. It was stated that each translation is a creative process and the main task of the translator is still to transmit the characteristic features of the original in translation in different ways, depending on translator himself. The article focuses on analysis of the gradations translation into Russian.